Dictionary of phrasal verbs (HarperCollins, 2002)
This second edition offers comprehensive coverage of the most important phrasal verbs in English. With up-to-date coverage of thousands of phrasal verbs, this second edition offers learners of English detailed help with this difficult language area. Thousands of examples of real English from the Bank of English provide essential guidance on context and usage. Attractively presented, and now with colour for additional clarity, this title should prove useful for all learners of English wishing to gain a fuller understanding of phrasal verbs and use them more effectively.